Environmental co-benefits of improved forages in smallholder dairy systems of Kenya - Notenbaert, An Maria Omer; Mwendia, Solomon W.; Burkart, Stefan; Karimi, Peggy; Musau, Emmanuel Mwema (International Grassland Congress 2023, 2023)
Livestock play a major role across Kenya, especially in smallholder mixed farms through provision of household nutrition and income through milk and meat. Equally, fertilization of cropland benefits from livestock manure, and livestock often act as insurance and saving. Despite the opportunities and benefits livestock production presents, livestock systems are also key drivers of environmental degradation, including increased nutrient loads, GHG emissions, water use, grassland degradation and land-use conversion. Low livestock productivity, largely due to use of low-quality crop residues and natural grasses often not endowed with nutrients key for animal performance, limits the potential positive contributions of livestock and at the same time reduces the efficiency of natural resource use. In response to this and with smallholder dairy farmers’ participation, we undertook an evaluation of 5 selected improved cultivated forages from Urochloa and Megathyrsus genus as an alternative to the Napier grass commonly grown by farmers. We evaluated impact on livestock productivity, farmers’ income, land and water requirement, soil erosion, soil health and greenhouse gas emissions. We observed more efficient use of farmers’ lands and financial resources through integrating improved forages and optimization of feeding strategies. We have also shown that the production and use of improved forages can act as a good climate change mitigation option.